Answer:
a. [tex]x^2-6x-8=0[/tex]
b. [tex]x^2-6x=8[/tex]
c.
[tex]\frac{1}{2}[/tex] (Coefficient of x) = [tex]\frac{-6}{2}=-3[/tex]
Also, [tex](-3)^2=9[/tex]
d. [tex]x^2-6x+9=17[/tex]
e. [tex](x-3)^2=17[/tex]
f, g. [tex]x=3\pm \sqrt{17}[/tex]
Step-by-step explanation:
Given: [tex]2x^2-12x-16=0[/tex]
To solve: the given equation
Solution:
a.
[tex]2x^2-12x-16=0[/tex]
Coefficient of [tex]x^2=2[/tex]
Divide both sides by 2
[tex]x^2-6x-8=0[/tex]
b.
[tex]x^2-6x=8[/tex]
c.
Coefficient of x = -6
[tex]\frac{1}{2}[/tex] (Coefficient of x) = [tex]\frac{-6}{2}=-3[/tex]
Also, [tex](-3)^2=9[/tex]
d.
Add 9 to both sides of the equation: [tex]x^2-6x=8[/tex]
[tex]x^2-6x+9=8+9\\x^2-6x+9=17[/tex]
e.
[tex]x^2-6x+9=17\\x^2-2(3)x+3^2=17\\(x-3)^2=17\,\,\left \{ \because (a-b)^2=a^2+b^2-2ab \right \}[/tex]
f.
[tex](x-3)^2=17\\x-3=\pm \sqrt{17}\\x=3\pm \sqrt{17}[/tex]
g.
[tex]x=3\pm \sqrt{17}[/tex]